2009
DOI: 10.1111/j.1439-0272.1992.tb02600.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and morphometric studies on the kinetics of germ cells and immature Sertoli cells during human prespermatogenesis*

Abstract: Summary. Human prespermatogenesis between the 8th week of pregnancy and six months after birth was studied in testis material of 28 male foetuses from spontaneous abortions and 81 infants who died from sudden infant death. The foetuses and infants were grouped in 10 age groups. A first steep raise in the numbers of germ cells per 20 tubular cross sections from 22.3 in the first group up to 69.5 in group 3 was observed, i.e. up to the end of the 22nd week of pregnancy. Thereafter, a continuous decrease could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…Another difference resides in the fact that rodent gonocyte undergoes two phases of proliferation in the fetal and neonatal periods, respectively, separated by a proportionally long period of quiescence, whereas humans and marmosets lack this quiescent phase, and instead, one can find proliferative gonocytes in all periods surveyed, from gestation weeks (GWs) 12-14 until 2.5-4 months after birth in human, albeit at various levels (Hilscher & Engemann 1992, Berensztein et al 2002, Honecker et al 2004, Ewen et al 2013. Overall, these studies reported the highest rates of proliferation between the third and fifth gestation months, followed by decreased proliferation in late gestation and a small increase in proliferation in 2.5-to 6-month-old infants.…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 99%
“…Another difference resides in the fact that rodent gonocyte undergoes two phases of proliferation in the fetal and neonatal periods, respectively, separated by a proportionally long period of quiescence, whereas humans and marmosets lack this quiescent phase, and instead, one can find proliferative gonocytes in all periods surveyed, from gestation weeks (GWs) 12-14 until 2.5-4 months after birth in human, albeit at various levels (Hilscher & Engemann 1992, Berensztein et al 2002, Honecker et al 2004, Ewen et al 2013. Overall, these studies reported the highest rates of proliferation between the third and fifth gestation months, followed by decreased proliferation in late gestation and a small increase in proliferation in 2.5-to 6-month-old infants.…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 99%
“…In an XY genital ridge, expression of the gene Sry from 10.5 dpc in pre-supporting cells triggers differentiation of Sertoli cells and the subsequent cascade of testis development (Koopman et al, 1991). Germ cells in the fetal testis environment become encased within the developing testis cords and are directed to enter the G 1 / G 0 phase of mitosis from 12.5 dpc, apparently marking their commitment to spermatogenesis (Hilscher 1974). In males, germ cells initiate meiosis postnatally.…”
Section: Cross-roads: Oogenesis or Spermatogenesis?mentioning
confidence: 99%
“…In the fetal ovary, entry into meiosis is seen as the first indication that germ cells have embarked on oogenesis (McLaren 1984). In a newly specified testis, germ cells enter a period of mitotic quiescence and remain in that state until just prior to puberty, when meiosis commences (Hilscher 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse fetal ovary, PGCs enter meiosis and commit to oogenesis, whereas in a fetal testis, they avoid entry into meiosis and instead undergo mitotic arrest and begin to differentiate towards spermatogenesis (Hilscher 1974;McLaren and Southee 1997). Recent studies have identified some of the key somatic factors involved in regulating fetal germ cell behavior appropriately (Barrios et al 2010;Bowles et al 2010;Bowles et al 2006;Koubova et al 2006).…”
Section: Introductionmentioning
confidence: 99%